#### Answer

(y-12)(y+4)

#### Work Step by Step

$y^{2}$-8y-48=$y^{2}$+4y-12y-48=y(y+4)-12(y+4)=
(y-12)(y+4)

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

(y-12)(y+4)

$y^{2}$-8y-48=$y^{2}$+4y-12y-48=y(y+4)-12(y+4)=
(y-12)(y+4)

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.